The Historical Implications of the Keraton Yogyakarta on the Conception of Place in the Jeron Beteng Area, Yogyakarta - Emmelia Tricia Herliana (Universitas Udayana, 2024)
The Sultanate of Yogyakarta has been a distinct part of the characters associated with Yogyakarta City. The Jeron Beteng area, which is administratively located in the District of Kraton, was in the past the center of this Sultanate. It becomes part of historical journeys that construct the identity of Yogyakarta city as a place. Since its confirmed status as a heritage zone, the Jeron Beteng continuously attracts increasing tourists. It becomes subject to continuous land use, traffic, migration, and land ownership changes. As a result, the identity of the place has been transformed unclearly. This study views that, understanding the conception of a Jeron Beteng area as a place is essential to preserve its identity. It explores the dynamics of this conception based on cultural significances derived from historical events between 1755 and the present time. The research question is